Tid för litteraturdidaktiskt paradigmskifte? - Andersson, Pär-Yngve (Tidskrift för litteraturvetenskap, 2010)
Time for a Paradigmatic Shift in Literature Didactics? An increasing number of literary scholars are involved in the didactic education of university students studying to become teachers. In this article I discuss the difficulties and possibilities of the task in a changing media landscape where reading fiction seems to be losing popularity. I argue that the paradigm in literature didactics has hitherto been rather one-sided, dominated by reader response-theory and pedagogy based on the high valuation of individual experience, but neglecting the learning of literary skills and strategies. However, several researchers have pointed to the fact that Swedish pupils seem to interpret texts in rather subjective ways, in a kind of private readings. They have difficulties in understanding fictional texts, especially when the aesthetic forms are unfamiliar. The study of literature didactics cannot be restricted to the reader response-paradigm, but must make use of other perspectives in literary theory. In my opinion, the future teachers have to provide a widening of their pupils’ horizons. They must read a great variety of literature together, talk and write about it, and discuss relevant interpretations. Teachers cannot neglect teaching aesthetics, and they must, beginning in the early years of schooling, explain to their pupils the value of literary reading. Learning literary strategies is important for anyone, but especially for low performing readers. I argue that literature has a potential for increasing the sense of individual freedom and cultivating one’s mind, but also that literary studies can provide argumentative skills and raise a critical consciousness. In the visual and interactive culture of our days, the study of literature can be an alternative opportunity where slowness and critical reflection is honoured.